Learn Azure Synapse Data Explorer A Guide to Building Real-Time Analytics Solutions to Unlock Log and Telemetry Data - Rocha, Pericles (Packt Publishing, Limited, 2023)
A hands-on guide to working on use cases helping you ingest, analyze, and serve insightful data from IoT as well as telemetry data sources using Azure Synapse Data Explorer Free PDF included with this book Key Features Augment advanced analytics projects with your IoT and application data Expand your existing Azure Synapse environments with unstructured data Build industry-level projects on integration, experimentation, and dashboarding with Azure Synapse Book Description Large volumes of data are generated daily from applications, websites, IoT devices, and other free-text, semi-structured data sources. Azure Synapse Data Explorer helps you collect, store, and analyze such data, and work with other analytical engines, such as Apache Spark, to develop advanced data science projects and maximize the value you extract from data. This book offers a comprehensive view of Azure Synapse Data Explorer, exploring not only the core scenarios of Data Explorer but also how it integrates within Azure Synapse. From data ingestion to data visualization and advanced analytics, you'll learn to take an end-to-end approach to maximize the value of unstructured data and drive powerful insights using data science capabilities. With real-world usage scenarios, you'll discover how to identify key projects where Azure Synapse Data Explorer can help you achieve your business goals. Throughout the chapters, you'll also find out how to manage big data as part of a software as a service (SaaS) platform, as well as tune, secure, and serve data to end users. By the end of this book, you'll have mastered the big data life cycle and you'll be able to implement advanced analytical scenarios from raw telemetry and log data. What you will learn Integrate Data Explorer pools with all other Azure Synapse services Create Data Explorer pools with Azure Synapse Studio and Azure Portal Ingest, analyze, and serve data to users using Azure Synapse pipelines Integrate Power BI and visualize data with Synapse Studio Configure Azure Machine Learning integration in Azure Synapse Manage cost and troubleshoot Data Explorer pools in Synapse Analytics Secure Synapse workspaces and grant access to Data Explorer pools Who this book is for If you are a data engineer, data analyst, or business analyst working with unstructured data and looking to learn how to maximize the value of such data, this book is for you. If you already have experience working with Azure Synapse and want to incorporate unstructured data into your data science project, you'll also find plenty of useful information in this book. To maximize your learning experience, familiarity with data and performing simple queries using SQL or KQL is recommended. Basic knowledge of Python will help you get more from the examples.